EFEKTIFITAS PENERAPAN BLENDED LEARNING DALAM MENINGKATKAN MOTIVASI BELAJAR MAHASISWA SASTRA INGGRIS UNIVERSITAS KHAIRUN - Magfirah, Sulmi (Universitas Negeri Makassar, 2020)
Abstract. Blended learning is a learning model that lecturers can apply to optimize the learning outcomes. This study, entitled